Phototrophic purple bacteria as feed supplement on the growth, feed utilization and body compositions of Malaysian mahseer, tor tambroides juveniles - Ahmed Jalal Khan Chowdhury,; Nor Hafizah Zakaria,; Zaima Azira Zainal Abidin,; Mohammad Mustafizur Rahman, (Universiti Kebangsaan Malaysia, 2016)
The application of microbial techniques in aquaculture has been playing a vital role to increase the production yield by improving the nutritional values of the targeted fish. Phototrophic purple bacteria as single cell protein (SCP) appears to be a promising substitution for protein rich supplement for aquaculture feeds making them a promising growth enhancer in aquaculture industry. Two species of phototrophic purple bacteria, Marichromatium sp. and Rhodopseudomonas sp. were used in the commercial diet to compare the growth, survival rate and feed utilizationon for Tor tambroides juvenile. Purple bacteria were isolated from mangrove sediment and fish tank and mass cultured using 112 synthetic media under anaerobic light condition. Bacterial cells were included in the diets by mixing the fresh biomass with the crushed commercial pellet, re-pelleted and air-dried. The experimental diets were fed to the fingerlings twice per day for 10 weeks to satiation level. The results showed that there were trends of increased growth, better survival rate and improved feed conversion ratio when fed with diet 1 (Marichromatium sp.) compared with other diets. There was significant difference (p<0.05) between the sampling days. The specific growth rate and weight gain of the fish fed with diet 1 were 0.49 % and 4.92 g, respectively, compared to 0.42% and 4.11 g from the control. This study suggested that purple bacteria could be used in feed formulation as a supplement to promote growth and survival of freshwater fishes in Malaysia.